Influência dos níveis plasmáticos de lipoproteína de alta densidade na inflamação cardiovascular, na resistência insulínica e no hemograma de camundongos knockout para o gene do receptor de LDL (LDLr-/-) - Messora, Luisa Barbosa (2010)
LDLr-/ - mice are spontaneously hyperlipidemic and resistant to the development of neointimal lesions. This study determined the influence of plasma levels of high density lipoprotein on cardiovascular inflammation, insulin resistance, and blood cell count in LDL (LDLr-/ -) receptor gene knockout mice. Three groups of 3-month-old male mice were used: Group WT, wild-type mice, Group S, LDLr-/ - mice fed a standard diet, Group HL, LDLr-/ - mice fed a hyperlipidic diet. After 15 days, blood was collected for analysis of plasma lipids, glucose, insulin, and hematological assays. The HOMA index was calculated to determine insulin resistance. The heart and aorta were removed and histologically processed. Heart sections were immunohistochemically processed with the anti-CD40L antibody to evaluate the inflammatory process. Artery sections were stained with hematoxylin-eosin and picrosirius red to assess morphological and morphometric changes. The S mice were resistant to inflammatory, had a low immunoreactivity to CD40L, high HDL plasma levels, and showed no insulin resistance, even with moderate hyperlipidemia in relation to WT. HL mice exhibited severe hyperlipidemia, increased immunoreactivity to CD40L, marked morphological alterations in the aorta wall, and insulin resistance, all associated with a decrease in HDL plasma levels in relation to S. The results showed a negative association between the plasma levels of high density lipoprotein and the total and differential leukocyte and platelet counts in the LDL receptor gene knockout mice. This ratio showed the important influence of the high density lipoprotein on the modulation of the immune and inflammatory response in dyslipidemias. Therefore, the evaluation of the blood cell count results, routinely correlated with the lipid plasma levels, can be promising in the prevention and prognosis of the severity of pathological conditions involving immune responses in dyslipidemias. The high HDL plasma level is a protective factor against the development of cardiovascular inflammation and insulin resistance in LDLr-/- mice, thus preventing the incidence of neointimal lesions.